2022
DOI: 10.1101/2022.10.17.512599
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transient and delay chemical master equations

Abstract: The serial nature of reactions involved in the RNA life-cycle motivates the incorporation of delays in models of transcriptional dynamics. The models couple a bursty or switching promoter to a fairly general set of Markovian or deterministically delayed monomolecular RNA interconversion reactions with no feedback. We provide numerical solutions for the RNA copy number distributions the models induce, and solve several systems with splicing and degradation. An analysis of single-cell and single-nucleus RNA sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 75 publications
(147 reference statements)
0
9
0
Order By: Relevance
“…The other one represents a single-nucleus RNA-seq experiment consisting of 4,000,000 nascent RNA reads and 1,000,000 mature RNA reads. The respective ratios of mature to nascent reads was estimated based on (Gorin, Yoshida, and Pachter 2022). The mature transcripts were obtained from version 104 of the Ensembl of GRCh38, and the nascent transcripts were taken to be the entire sequence from the start of the first exon through the end of the last exon.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other one represents a single-nucleus RNA-seq experiment consisting of 4,000,000 nascent RNA reads and 1,000,000 mature RNA reads. The respective ratios of mature to nascent reads was estimated based on (Gorin, Yoshida, and Pachter 2022). The mature transcripts were obtained from version 104 of the Ensembl of GRCh38, and the nascent transcripts were taken to be the entire sequence from the start of the first exon through the end of the last exon.…”
Section: Methodsmentioning
confidence: 99%
“…The utility of single-cell RNA-seq measurements for defining cell types has represented a marked improvement over bulk RNA-seq, and is driving rapid adoption of single-cell RNA-seq assays (Zeng 2022). Another application of single-cell RNA-seq that is not possible with bulk RNA-seq is the study of cell transitions and transcription dynamics, even via snapshot single-cell RNA-seq experiments (Gorin et al 2022). This novel application of single-cell RNA-seq is based on the quantification of both nascent and mature mRNAs (Figure 1a), lending import to the computational problem of accurately quantifying these two modalities.…”
Section: Introductionmentioning
confidence: 99%
“…However, in spite of its limitations and assumptions, the simple Markovian two-stage model has been successful in the past [61, 62]. Mechanistic evidence does not suggest that, e.g., deterministic delayed elongation is necessary to represent β€œunspliced” distributions [63]: under this model, we appear to be able to treat splicing and degradation as Markovian, without representing the elongation process at all, and obtain reasonable fits to the data. Somewhat surprisingly [64], the geometric-Poisson distribution, which describes bursty transcription coupled to deterministic elongation [65], is a particularly poor fit for unspliced RNA counts [63].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, comparisons of paired single-cell and single-nucleus datasets are hampered by the limited characterization of the noise sources in the latter technology. Yet again, we have generally found that omitting this effect in single-cell data produces acceptable fits [61– 63].…”
Section: Methodsmentioning
confidence: 99%
“…To generate synthetic data for Figure 1, we simulated a system with π‘˜ π‘œπ‘› = 0.15, π‘˜ π‘œ 𝑓 𝑓 = 0.1, π‘˜ 𝑑 π‘₯ = 20, and 𝛾 = 3.14 using Gillespie's stochastic simulation algorithm (17), as previously implemented for (18). We performed 1,000 simulations, run until 𝑑 = 5, with the system state stored at 200 uniformly spaced time points (Δ𝑑 = 0.025).…”
Section: Methodsmentioning
confidence: 99%